Nutritional habits and performance in male elite wheelchair basketball players during a precompetitive period - Ferro, A.; Garrido, G.; Villacieros, J.; Pérez, J.; Grams, L. (Adapted Physical Activity Quarterly, 2017)
Physical condition and an optimized diet are relevant to enhance performance and recovery. The diet composition and meal frequency of eleven elite wheelchair basketball players were estimated using a 3-day food-weighing diary in two months during the precompetitive-period. Performance was determined through a 20 m sprint test. The players consumed 4.2 ± 0.8 meals/day in May and 4.5 ± 0.9 meals/day in June, resulting in total energy intakes of 2492 ± 362 kcal/d and 2470 ± 497 kcal/d, respectively. The macronutrient distribution was 3.8 ± 1.3 g/kg carbohydrates, 1.7 ± 0.6 g/kg protein, and 36 ± 5% of energy derived from fat in May, and 4.2 ± 1.9 g/kg carbohydrates, 1.5 ± 0.5 g/kg protein and 32 ± 5% of energy derived from fat in June. The maximum velocity of the sprint test improved from 4.77 ± 0.31 m/s in May to 5.19 ± 0.23 m/s in June. Our results revealed carbohydrate intake below and fat intake above recommendations, but improvements of dietary patterns. Further nutritional advice is necessary to ensure health and performance improvements.